2000
DOI: 10.1175/1520-0493(2000)128<1899:apvtda>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Vorticity Tendency Diagnostic Approach for Tropical Cyclone Motion*

Abstract: In order to understand the roles of various physical processes in baroclinic tropical cyclone (TC) motion and the vertical coupling between the upper-and lower-level circulations, a new dynamical framework is advanced. A TC is treated as a positive potential vorticity (PV) anomaly from environmental flows, and its motion is linked to the positive PV tendency. It is shown that a baroclinic TC moves to the region where the azimuthal wavenumber one component of the PV tendency reaches a maximum, but does not nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
128
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(135 citation statements)
references
References 47 publications
5
128
0
2
Order By: Relevance
“…Note that in the present study, we found that the vorticity tendency (VT) approach is appropriate since the TC track is consistent with the VT, similar to that applied to TC motion, such as northwestward beta drift (e.g., Holland, 1983) and shear effects (e.g., Wu and Emanuel, 1993). The PV Tendency (PVT) diagnostic approach, as originally proposed by Wu and Wang (2000) and Chan et al (2002) and applied to real-case simulations (e.g., Hsu et al, 2013;Chan, 2013, 2014;Wang et al, 2013), appears to be an attractive method and will be considered in our future research. …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Note that in the present study, we found that the vorticity tendency (VT) approach is appropriate since the TC track is consistent with the VT, similar to that applied to TC motion, such as northwestward beta drift (e.g., Holland, 1983) and shear effects (e.g., Wu and Emanuel, 1993). The PV Tendency (PVT) diagnostic approach, as originally proposed by Wu and Wang (2000) and Chan et al (2002) and applied to real-case simulations (e.g., Hsu et al, 2013;Chan, 2013, 2014;Wang et al, 2013), appears to be an attractive method and will be considered in our future research. …”
Section: Discussionsupporting
confidence: 66%
“…In addition, unlike a dry cyclone vortex used in LS11 and L05, a more realistic bogus TC is initiated in a conditionally unstable atmosphere with land surface, moist and planetary boundary layer (PBL) processes included. A vorticity budget analysis is adopted to help understand the effects of combined forcing of orography and convection, instead of the potential vorticity tendency (PVT) diagnostic approach taken by some previous studies (e.g., Wu and Wang, 2000;Chan et al, 2002;Hsu et al, 2013;Chan, 2013, 2014;Wang et al, 2013). The direct diabatic heating effects will be investigated along with the rainfall distributions.…”
Section: Introductionmentioning
confidence: 99%
“…60초 간격으로 72시간 동안 적분을 하였다. 물리과 정으로, 적운 모수화에는 Kain-Fritsch scheme이 이 용되었고 (Kain and Fritsch, 1993), 경계층 모수화에 (Wu and Wang, 2000;Chan et al, 2002;Wong and Chan, 2006). 시그마좌표계에서 파수 1 성분의 잠재와도 경 향방정식은 다음 식(1)과 같이 나타낼 수 있다 (Wu and Wang, 2000).…”
Section: 한국기상학회 대기 제26권 4호 (2016)unclassified
“…물리과 정으로, 적운 모수화에는 Kain-Fritsch scheme이 이 용되었고 (Kain and Fritsch, 1993), 경계층 모수화에 (Wu and Wang, 2000;Chan et al, 2002;Wong and Chan, 2006). 시그마좌표계에서 파수 1 성분의 잠재와도 경 향방정식은 다음 식(1)과 같이 나타낼 수 있다 (Wu and Wang, 2000). (Fiorino and Elsberry, 1989;Wang and Holland 1996a, 1996b, 1996cChan and Cheung, 1998;Wong and Chan, 2006).…”
Section: 한국기상학회 대기 제26권 4호 (2016)unclassified
“…The PV perspective is not only applicable to TC motion (e.g., Wu and Wang, 2000;Chan et al, 2002;Choi et al, 2013), but also to TC intensity change (e.g., Molinari et al, 1998). Molinari et al (1998Molinari et al ( , 1995 also applied the PV perspective to interaction cases, in which interaction could be viewed as an upper-level synoptic PV anomaly (the environment) interacting with a lower-level mesoscale PV anomaly (the TC).…”
Section: Tc Interactionmentioning
confidence: 99%